2021
DOI: 10.1101/2020.12.29.20248869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High levels of plasminogen activator inhibitor-1, tissue plasminogen activator and fibrinogen in patients with severe COVID-19

Abstract: We measured plasma levels of fibrinogen, plasminogen, tissue plasminogen activator (t-PA) and plasminogen activation inhibitor 1 (PAI-1) in blood from 37 patients with severe coronavirus disease-19 (COVID-19) and 23 controls. PAI-1, t-PA and fibrinogen levels were significantly higher in the COVID-19 group. Increased levels of PAI-1 likely result in lower plasmin activity and hence decreased fibrinolysis. These observations provide a partial explanation for the fibrin-mediated increase in blood viscosity and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…While Umemura et al reported an unchanged PAI-1 level in COVID-19 patients 52 , several other groups detected the increased levels of PAI-1, tPA and uPA in COVID-19 patients as compared to heathy controls 53,54 . Zou and co-authors demonstrated that high levels of tPA and PAI-1 were associated with worse respiratory status in patients hospitalized with COVID-19 48 .…”
Section: Discussionmentioning
confidence: 91%
“…While Umemura et al reported an unchanged PAI-1 level in COVID-19 patients 52 , several other groups detected the increased levels of PAI-1, tPA and uPA in COVID-19 patients as compared to heathy controls 53,54 . Zou and co-authors demonstrated that high levels of tPA and PAI-1 were associated with worse respiratory status in patients hospitalized with COVID-19 48 .…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, earlier reports suggest that elevated levels of plasminogen activator inhibitor type 1 (PAI-1), which is one of the most important inhibitors of the fibrinolytic system, may result in lower plasmin activity and hence decreased fibrinolysis. This in turn, may contribute to an imbalance between coagulation and fibrinolysis in COVID-19 (23).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperfibrinolysis resulting from excessive plasmin activity is also associated with elevated D-dimer in severely-ill COVID-19 patients. While Umemura et al reported an unchanged PAI-1 level in COVID-19 patients [54], several other groups detected the increased levels of PAI-1, tPA and uPA in COVID-19 patients as compared to heathy controls [55,56]. Zou and co-authors demonstrated that high levels of tPA and PAI-1 were associated with worse respiratory status in patients hospitalized with COVID-19 [50].…”
Section: Plos Onementioning
confidence: 96%